Poverty in the 21st Century: A Critique of Dominant Paradigms and Alternative Perspectives for Developing Countries - The Case of Morocco - Kharouaa, Achraf; Aoujil, Ali (European Scientific Journal, ESJ, 2025)
This article critically examines why poverty persists despite three decades of prioritized anti-poverty policies, particularly in developing countries like Morocco. It argues that conceptual and epistemological limitations of dominant poverty paradigms constrain policy effectiveness when addressing cumulative socio-economic challenges. Through a critical analysis of poverty conceptualizations and their evolution, the paper deconstructs implicit assumptions underlying anti-poverty policies, revealing significant blind spots: the myth of automatic inclusive growth, technocratic depoliticization of poverty issues, and underestimation of structural factors. Morocco serves as an illustrative case study, demonstrating how, despite notable progress in reducing monetary poverty, persistent vulnerabilities and inequalities reveal the limitations of conventional approaches. The article proposes reconceptualizing poverty through relational and political perspectives that acknowledge power structures and systemic factors, advocating for transformative rather than compensatory policies. For Morocco specifically, this implies rethinking the social contract, strengthening local solidarity innovations, and balancing institutional reforms with social mobilization to achieve sustainable socio-economic transformation.